IMPLEMENTASI TEKNIK ALONG PATH ANIMATION SEBAGAI MEDIA SIMULASI VISUAL JALUR TRANS BANYUMAS - Danu Iqbal Maulana; Dani Arifudin; Suliswaningsih (LPPM Universitas Abdurrab, 2026)
This study implements the Along Path Animation technique to visualize the Trans Banyumas bus route, aiming to present travel flow and route direction in a clear, consistent, and accurate visual simulation. The study is motivated by a decline in Trans Banyumas ridership, which has been associated with limited access to and clarity of service information related to routes, travel flow, and operational procedures. Media development was conducted using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Visual assets were designed and animated using Adobe After Effects, applying the Along Path Animation technique to enable the bus object to move precisely along predefined route paths. The animation was evaluated through alpha testing and expert validation, focusing on technical aspects such as motion smoothness, path accuracy, orientation consistency, visual synchronization, and overall animation performance. The results indicate that the application of Along Path Animation reduced the number of keyframes from 17 to 9, or approximately 47%, improving motion consistency and production efficiency. Overall, the technique is considered reliable and practical for public transportation route visualization. Future research is recommended to involve end-user testing and real-time mobility data integration to further assess animation effectiveness.